Renal profile of COVID-19 infected patients admitted in a tertiary care hospital in Western Rajasthan - Sharma, Pradeep K.; Aggarwal, Vikas; Sapariya, Naresh; Baweja, Shekhar; Nagori, Rupesh; Chabbra, M. K. (International Surgery Journal, 2020)
Background: A recent cluster of pneumonia cases all over the world including India, is caused by a novel beta coronavirus, the 2019 novel coronavirus (2019-nCoV). The objective of this study was to observe the effect on renal profiles at admission of these COVID-19 infected patients. Methods: All the patients were admitted to Dr. S. N. Medical College and Hospital, Jodhpur, a tertiary care hospital of Western Rajasthan and were tested for COVID-19 by real time reverse transcription polymerase chain reaction assay of 2019-nCoVRNA. All data in relation to patients including blood renal profile were collected from data collection form from electronic medical records and history given by COVID-19 infected patients admitted. Results: Out of total 300 COVID-19 patients, majority of patient were male i.e. 210 (70%) and majority of the patients 70% were below 60 years of age. The underlying diseases were present in 98 (32.67%) patients. Cough was the most common symptom (80%) followed by fever (72%) in out of 180 (60%) symptomatic patients. 64 (21.3%) patients had deranged renal function tests with abnormal blood urea nitrogen and serum creatinine. Overall, 56 patients (18.6%) without chronic kidney disease showed mild increase of BUN or serum creatinine. 35 patients (11.6%) had high blood urea nitrogen and 18 patients (6%) had raised creatinine. Conclusions: In setting of COVID-19 infected patient’s presentation, renal profile remained essentially normal with deranged RFT seen in patients with comorbidities. Nevertheless, the renal function of patients with COVID-19 needs to be monitored regularly, especially in patients with elevated plasma creatinine.